An EFSUMB Introduction into Dynamic Contrast-Enhanced Ultrasound (DCE-US) for Quantification of Tumour Perfusion - Dietrich, C. F.; Averkiou, M. A.; Correas, J.-M.; Lassau, N.; Leen, E.; Piscaglia, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Dynamic Contrast Enhanced Ultrasound (DCE-US) is an imaging technique that utilizes microbubble contrast agents in diagnostic ultrasound. The EFSUMB guidelines published in 2004, updated in 2008 and 2011 focused on the use of DCE-US, including essential technical requirements, training, investigational procedures and steps, guidance on image interpretation, established and recommended clinical indications and safety considerations. However the quantification of images acquired with ultrasound contrast agents (UCAs) is not discussed in the guidelines. The purpose of this EFSUMB document is to provide some recommendations and descriptions of the quantification of ultrasound images, technical requirements for analysis of time-intensity curves (TICs), methodology for data analysis, and interpretation of the results.
Keywords: Ultrasound contrast agents; guidelines; therapy monitoring; perfusion quantification